Implementación de un sistema SCADA para el control de temperatura de dos hornos a través de una red ethernet. - López Herrera, Joseph Michael (2021)
Currently, the control of industrial processes is one of the areas that they take great relevance due to the rise of automation by applying machinery and technological equipment that use software in order to carry out all types of production process. The current proposal suggests the application of a SCADA system for the temperature control of two furnaces through an Ethernet network to develop practical skills in the professional field, and conduct the monitoring and control of temperature processes by employing Ethernet communication networks. Furthermore, this present project was focused on each student because they can be in a family environment with an industrial process during it may be executed. This research project will allow access to settings, electrical connections, control and monitoring of variables to be operated and that make up the automatic control system which will permit to improve qualified skills by acquiring more knowledge according to the control systems. Thus, in their professional stage they will face with several procedures and sorts of instrumentation and automation. Therefore, two furnaces are built with a tubular resistance as heating element by using two PLCs they have control of each of them through an Ethernet network to observe their parameters by developing a SCADA system implemented in Ignition, and as a result comparisons and behavior of temperature variables will be performed.